Teologi Keluarga: Kajian Terhadap Kejadian 1-3 Sebagai Dasar Pemahaman Esensi Keluarga Kristen - Bakhoh Jatmiko (SANCTUM DOMINE: JURNAL TEOLOGI, 2018)
Family is an intersting entity to study. Theologically, a family is a God established intitution in the marrital bound between a man and a woman. The family that designed by God himself has been through many threads and challenges from the world that promoting new values for the family that makes the family origin values put by God are being faded out. Many distortions in the family have become challenges for the church and the believers to set the focus to a family as mentioned in the Bible especially Genesis 1-3 as a resources where Christians capture the picture of the first family that have ever existed.